The assembly and annotation of two teinturier grapevine varieties, Dakapo and Rubired - Eleanore J. Ritter; Noé Cochetel; Andrea Minio; Peter Cousins; Dario Cantu; Chad Niederhuth (GigaByte)
Teinturier grapevines, known for their pigmented flesh berries due to anthocyanin production, are valuable for enhancing the pigmentation of wine, for potential health benefits, and for investigating anthocyanin production in plants. Here, we assembled and annotated the Dakapo and Rubired genomes, two teinturier varieties. For Dakapo, we combined Nanopore sequencing, Illumina sequencing, and scaffolding to the existing grapevine assembly to generate a final assembly of 508.5 Mbp. Combining de novo annotation and lifting over annotations from the existing grapevine reference produced annotation 36,940 gene annotations for Dakapo. For Rubired, PacBio HiFi reads were assembled, scaffolded, and phased to generate a diploid assembly with two haplotypes 474.7–476.0 Mbp long. De novo annotation of the diploid Rubired genome yielded annotations for 56,681 genes. Both genomes are highly contiguous and complete. The Dakapo and Rubired genome assemblies provide genetic resources for investigations into berry flesh pigmentation and other traits of interest in grapevine.